The ecology and integrated management of broom (Cytisus scoparius) in New Zealand plantation forests : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Manawatu, New Zealand - Tran, Hop (Massey University, 2013)
Broom (Cytisus scoparius) is a major weed of radiata pine (Pinus radiata) plantations in New Zealand. The objective of this work was to determine how best to discourage broom establishing successfully within newly planted pine forests. Measurements of seed banks under pine forests showed that broom seeds can accumulate in the soil prior to the trees being harvested, with over 3500 seeds m–2 of high viability being found in some forest soils. Seeds germinate immediately once scarified, but unscarified seeds break dormancy over time, and temperature fluctuations within bare soil are thought to help break seed coats. A field trial in which several different grass species were sown at different rates showed that grasses establishing at the same time as broom seedlings have little detrimental effect on broom establishment, regardless of whether planted in spring or autumn. However, if grasses had been established for six months prior to broom seeds germinating, no broom survived. A range of herbicides were tested for their ability to control broom from three months to 12 months in age. Most herbicides tested gave good control of broom seedlings, including hexazinone, terbuthylazine, and several combinations of clopyralid, triclopyr and picloram, though some herbicides were better than others on older plants. Herbicides were also assessed to determine how persistent they are within soil for controlling broom seedlings that begin establishing several months after a herbicide was applied. Three of the most persistent treatments were hexazinone, clopyralid and a triclopyr/picloram mixture. A range of herbicide and ground cover treatments were assessed in a newly planted pine forest in Hawkes Bay for their effect on broom establishment. The most effective strategy for discouraging broom problems in pine forests is thought to involve planting grass ground covers then using a herbicide mixture based on clopyralid with some picloram and triclopyr added to selectively remove broom from among young pines and the grass sward within the first 12 months. Following this herbicide application, subsequent establishment of further broom seedlings should be prevented initially by residues from the herbicide then later by the grass sward.
Keywords: Scotch broom; Cytisus scoparius